Cane Hay Cost-Return Budget (W-CH-F Rotation) in Western Kansas - O'Brien, Daniel M.; Dumler, Troy J. (My University, 1999)
This publication estimates the costs and returns associated with a typical sorghum sudangrass hybrid planted at heavier seeding rates and harvested as a hay crop in western Kansas.
MF997_1999_10
Keywords: MF997; Economics; Crops; MF